The eye [videorecording (DVD)] - Carlton, Emily; Haasan, Shruti; Rowley, Mark, 1990-; Sawa, Anna (Freestyle Digital Media, 2026)
A grieving widow's return to a remote island leads to a harrowing choice between reality, myth, and murder.